Optimizing the Role of BUMDes Through The Utilization of Herbal Chili Production Potential in Pekandangan Tengah Village, Bluto District, Sumenep Regency - Djulaeka, Djulaeka; Zulkifli, Makhmud (LPPM Universitas Trunojoyo Madura, 2023)
This study aims to see or measure the financial performance of BUMDes Bina Sejahtera in Pekandangan Tengah village, Bluto sub-district, Sumenep district, which is expected to be able to improve village welfare through contributions to village original income obtained from BUMDes contributions. This research is a qualitative and quantitative descriptive study by looking at the economic potential of the village and the performance of BUMDes through the ROE (return on equity) ratio. Samples were taken from herbal chili farmers as many as 10 people by purposive sampling and 1 BUMDes. The results of this study indicate that the income of herbal chili farmers is quite good but their sales are through middlemen or agents, while the performance of BUMDes with ROE benchmarks below 2% per year has not contributed to the village's original income (PADes).